En bloc kidney transplant from pediatric donor to an adult - Singh, Navdeep; Elkhammas, Elmahdi; Rajab, Amer (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
The use of pediatric kidney donors is not a common practice. Transplant physicians and surgeons are concerned with technical issues as well as inadequate nephrons mass. We reported a case of en bloc kidney transplant from a pediatric donor to serve as a teaching case. The donor is a 3-year-old infant who died as a result of influenza. Due to the age and size discrepancy with an adult, it was decided to transplant the kidneys en bloc into an adult with successful outcome. En bloc technique renders the kidneys transplantable which would have been otherwise discarded and theoretically protect against hyperfiltration injury. Small pediatric donors are excellent resources and should be considered for donation whenever option is available.
Keywords: En bloc kidney transplant; end-stage renal disease; glomerular filtration rate; inferior vena cava; kidney transplantation; single kidney transplant; standard criteria donor transplant